Metagenomic insights into the antibiotic resistomes of typical Chinese dairy farm environments - Kang, Jijun; Liu, Yiming; Chen, Xiaojie; Xu, Fei; Wang, Honglei; Xiong, Wenguang; Li, Xiubo (Frontiers in Microbiology, 2022)
Antibiotic resistance genes (ARGs) in the environment pose a threat to human and animal health. Dairy cows are important livestock in China; however, a comprehensive understanding of antibiotic resistance in their production environment has not been well clarified. In this study, we used metagenomic methods to analyze the resistomes, microbiomes, and potential ARG bacterial hosts in typical dairy farm environments (including feces, wastewater, and soil). The ARGs resistant to tetracyclines, MLS, β-lactams, aminoglycoside, and multidrug was dominant in the dairy farm ecosystem. The abundance and diversity of total ARGs in dairy feces and wastewater were significantly higher than in soil (P<0.05). The same environmental samples from different dairy have similar resistomes and microbiomes. A high detection rate of tet(X) in wastewater and feces (100% and 71.4%, respectively), high abundance (range from 5.74 to 68.99 copies/Gb), and the finding of tet(X5) challenged the clinical application of the last antibiotics resort of tigecycline. Network analysis identified Bacteroides as the dominant genus in feces and wastewater, which harbored the greatest abundance of their respective total ARG coverage and shared ARGs. These results improved our understanding of ARG profiles and their bacterial hosts in dairy farm environments and provided a basis for further surveillance.